Uji Penghambatan Tirosinase dan Stabilitas Fisik Sediaan Krim Pemutih yang Mengandung Ekstrak Kulit Batang Nangka (Artocarpus heterophyllus) - Juwita, Ninin Kartika; Djajadisastra, Joshita; Azizahwati, Azizahwati (UI Scholars Hub, 2011)
The cortex of jackfruit (Artocarpus heterophyllus) contains some flavonoids which have activity as tyrosinase inhibitors. This compound can inhibit the oxidation of l-tyrosine and levodopa in the mechanism of melanogenesis. The extract of jackfruit cortex formulated into creams differentiated by the extract concentration of 1,5% and 2,0%. Physical stability test was conducted with storing the creams at three different temperatures, 7 ± 2°, 27 ± 2°, and 40±2°C respectively. Centrifugal tests and cycling test was also performed on both cream. Tyrosinase inhibitory activity measurement was done by in vitro studies with measuring dopachrome. The result showed that both of formulations which stored at 40±2°C and centrifugated at 3800 rpm for 5 hours were not stable. The result of tyrosinase inhibiton activity measurement of creams containing extract of 1,5% and 2,0 % were 10,64% and 11,34%, respectively. Tyrosinase inhibition activity of creams decreased after two month stored. Tyrosinase inhibition activity of cream containing 1,5%extract decreased into 6,93%, and cream containing 2,0%extract decreased into 7,74%. The decreasing of tyrosinase inhibition activity is caused by the small amount of antioxidant is not enough to prevent oxidation of active ingredient.